Modelo murino de lesão hepática e renal induzida por acetaminofeno: efeitos da silimarina, glutamina, acupuntura e eletroacupuntura - Costa, Graciana Teixeira (2019)
Murine model of acetaminophen-induced liver and kidney injury: effects of silymarin, glutamine, acupuncture and electroacupuncture. Graciana Teixeira Costa. Doctor´s degree. Post-graduation Program Stricto Sensu in Medical-Surgical Sciences. Federal University of Ceará. Professor: Prof. Dr. Sérgio Botelho Guimarães. Acetaminophen overdose (APAP) results in the leading cause of induced liver failure and probably also acute renal failure. Therefore, as preclinical investigations of changes in APAP-induced liver and renal injury using animal models are very important. This study aims to identify the main hepatic, renal and plasma parameters changes involved in the treatment with silymarin, glutamine, acupuncture and electroacupuncture of acute and subacute injury in rats. One hundred and four Wistar rats were divided into two APAP injury models, called preconditioning and postconditioning. In the first, the groups were pretreated and then injury-induced, in the second, the groups were injury-induced and then posttreated. Each model was subdivided into seven subgroups: Negative Control saline (CN), Positive Control (CP), Silymarin 25 mg / kg (SLM), Glutamine 1g / kg (GLN), Acupuncture (ACP), Electroacupuncture 2Hz (EA2), Electroacupuncture 100Hz (EA100). The injury was induced with a dose of 3 g / kg APAP. The CN and CP groups received a 2 mL dose of saline. The experiments lasted eight days and the next day, blood collection and organ removal (liver and kidney) were performed for histopathological analysis. Plasma and tissue levels of AST, ALT, Urea, Creatinine, MPO, MDA, nitrite, GSH, cholesterol and fractions and triglycerides were measured. The injury caused liver toxicity with irreversible tissue destruction and renal toxicity without severe histological damage. The treatments attenuated in the preconditioning model: (1) liver: toxicity (SLM, EA2), oxidative stress (SLM, GLN, ACP, EA2, EA100) and histopathological changes (GLN, ACP, EA2, EA100), (2) kidney: toxicity (SLM, EA2, EA100), oxidative stress (SLM, GLN, ACP, EA2, EA100) and histopathological changes (GLN), (3) plasma: oxidative stress (SLM, G4, ACP, EA2, EA100); and postconditioning: (1) liver: toxicity (GLN, ACP), oxidative stress (SLM, GLN, ACP, EA2, EA100) and histopathological changes (SLM, ACP, EA2, EA100), (2) kidney: oxidative stress (SLM, GLN, ACP, EA2, EA100) and histopathological changes (SLM), (3) plasma: oxidative stress (ACP, EA2, EA100). The results observed in this study differ from liver and kidney injury inury models and can probably be attributed to hepatic exhaustion, which results in loss of membrane permeability due to reduction in cholesterol content. Inhibition or blockage of pro-regenerative pathways at higher doses of APAP by a mechanism not yet fully understood seems to influence acute hepatic and renal pathogenesis. Descriptors: Acetaminophen; Oxidative Stress; Liver Enzymes; Liver Injury; Kidney Injury; Drug Induction.